Strategic environmental policies in the presence of foreign direct investment - M. Ozgur Kayalica; Sajal Lahiri (Fondazione Eni Enrico Mattei (FEEM), 2001)
We analyse strategic environmental standards in the presence of foreign direct investment (FDI). A foreign firm located in a host country competes with a domestic firm in another country to export a homogeneous good to a third country. We also extend the model to allow the number of FDI to be endogenous. When the number of foreign firms is exogenous, the FDI host country always applies stricter environmental regulation. However, under free entry and exit of foreign firms, the FDI host country may apply lower standards under both non-cooperative and cooperative equilibrium.
Keywords: F2; H2; 330; Environment; emission permits; Foreign Direct Investment; trade; pollution; Umweltpolitik; Umweltstandard; Direktinvestition; Standortwettbewerb; Theorie